Dampak Kualitas Produk, Harga dan Kualitas Pelayanan pada Loyalitas Konsumen pada Counter Tectona 2 Cell Purwodadi - Akhmad Nurrofi (STIE Widya Manggala, 2022)
This study aims to determine how much influence product quality, price and service quality have on consumer loyalty at Counter Tectona 2 Cell. This research method uses primary data collection. The population in this study were all consumers at the Purwodadi Cellular Counter Tectona 2 Cell. The sampling technique used purposive sampling method with a total sample of 94 people. The data collection technique used a questionnaire that had been tested for validity and reliability and the data analysis technique used was multiple regression. The results showed that product quality had a significant effect on consumer loyalty. This is evidenced by the t arithmetic value of 3.739 with a significant value of 0.009 less than 0.05 (0.000 < 0.05), and the regression coefficient has a positive value of 0.323; (2) Price has a significant effect on consumer loyalty. This is evidenced by the t-count value of 2.638 with a significant value of 0.000 less than 0.05 (0.000 <0.05), and the regression coefficient has a positive value of 0.251; (3) Service quality has a significant effect on consumer loyalty. This is evidenced by the t- count value of 1.660. which means that the t-count value is greater than the t-table value, namely 3.888> 1.660, while the significance value is 0.000 <0.05, and the regression coefficient has a positive value of 0.375.